Fugitive democracy and other essays - Wolin, Sheldon S. (Princeton University Press, 2018)
Sheldon Wolin was one of the most influential and original political thinkers of the past 50 years. 'Fugitive Democracy' brings together his most important writings, from classic essays such as 'Political Theory as a Vocation, ' written amid the Cold War and the conflict in Vietnam, to his late radical essays on American democracy such as 'Fugitive Democracy, ' in which he offers a controversial reinterpretation of democracy as an episodic phenomenon distinct from the routinised political management that passes for democracy today.